Empowerment of women and its impact on population - Leela Visaria (Asia-Pacific Population Journal, 2012)
The data presented in this article from selected Asian and Pacific countries show that in the last two decades women have gained significantly in economic and social spheres, such as literacy, enrolment rates, gender inequality in education, age at marriage and participation in formal economic activities. Along with improvements in these empowerment measures, the region has also experienced substantial reductions in fertility, infant and child mortality, and maternal mortality and reported increases in use of contraception. However, not all countries in the Asian and Pacific region have made enough or equal progress in empowering women. Compared with women in many countries in East and South-East Asia, a significant proportion of young South Asian women remain deprived of education beyond the primary level and marry early, with adverse implications for their own health and that of their children.